Microstructure stability and damage mechanisms in an α/β Ti-6Al-4V-0.55Fe alloy during low cycle dwell-fatigue at room temperature. (February 2022) - Shi, Shan; Deng, Qinghua; Zhang, Hang; Feng, Liang; Xu, Xiangjun; Ding, Jie; Chang, Hui; Zhou, Lian
Highlights: The cyclic behavior and microstructure evolution of TC4F alloy were investigated. Phase transformations and α dynamic recrystallization contributed to great changes in the microstructure of TC4F alloy. The evolution of substructure played an important role in the dwell-fatigue of TC4F alloy. Abstract: The cyclic behavior and microstructure evolution of Ti-6Al-4V-0.55Fe alloy were investigated with three different total strain amplitudes. A slight softening was occurred with Δ εt /2 = 1.20%, and the alloy mainly suffered α recrystallization. Besides, a gentle softening can be observed with Δ εt /2 = 1.60%, which led to more substructure deformation. Furthermore, a sudden drop of the stress amplitude was occurred with Δ εt /2 = 4.00% which resulted in more plastic deformation. The phase transformation and α recrystallization were observed. Cracks were propagated along the α grain boundaries and the α/β lamellar interfaces due to the concentrated dislocations at the α/β lamellar interfaces.